MODELS OF TRANSLATING SOMATIC COMPONENT PROVERBS FROM DARI INTO UZBEK - Nargizakhon Mirakhatova (European International Journal of Multidisciplinary Research and Management Studies, 2026)
This article presents some of the Dari proverbs that include the somatic components that make up the main system of Dari language, compares them with Uzbek proverbs, analyzes their translation and alternative versions, and uses traditional translation methods.